Potentiating Antibody-Dependent Cellular Cytotoxicity in Triple-Negative Breast Cancer via the Humanized Anti-CD147 Antibody - Kanyarat Thongheang; Thanathat Pamonsupornwichit; Kanokporn Sornsuwan; On-anong Juntit; Tawan Chokepaichitkool; Weeraya Thongkum; Umpa Yasamut; Chatchai Tayapiwatana (Antibodies, 2025)
Background: Triple-negative breast cancer (TNBC) is an aggressive subtype with high metastatic potential, poor prognosis, and the absence of estrogen receptors, progesterone receptors, and human epidermal growth factor receptor 2 (HER2). The lack of these receptors limits the standard treatments, such as hormone therapies and HER2-targeted antibodies like trastuzumab. These challenges highlight the critical need for novel therapeutic strategies. CD147, a transmembrane glycoprotein overexpressed in TNBC, promotes tumor progression, metastasis, and chemoresistance, making it a promising therapeutic target. This study evaluates the antibody-dependent cellular cytotoxicity (ADCC) of HuM6-1B9, a humanized anti-CD147 antibody, against MDA-MB-231 cells, a TNBC model. Methods: CFSE-labelled MDA-MB-231 cells were co-cultured with PBMCs as effector cells (E:T ratio 80:1) in the presence of HuM6-1B9 and incubated for 4 h. Cells were then collected and stained with PI, and CFSE+/PI+ dead target cells were analyzed by flow cytometry. Results: Co-culturing MDA-MB-231 cells with peripheral blood mononuclear cells (PBMCs) in the presence of HuM6-1B9 demonstrated effective ADCC induction without direct cytotoxicity. HuM6-1B9 induced 54.01% cancer cell death via ADCC, significantly outperforming trastuzumab (26.14%) while sparing PBMCs. Conclusion: These findings support HuM6-1B9 as a prospective TNBC therapeutic and warrant further investigation into its clinical potential.